Productivity vs. Management: What Matters in the Export Process? - Argañaraz, Facundo Nahuel (2018)
In this paper, both a theoretical and an empirical model to study the contribution of productivity and management practices on exporter status are presented. On the theoretical side, a multiple heterogeneity model is developed, where firms can differ in their levels of two different kinds of productivity: in cost (φ) and in management (ζ), in a context of monopolistic competition. With this, in the autarkic case, the model achieves two conditions (Zero Cut-Off Profit Condition and Free Entry Condition) that firstly determine which firms enter and produce in the market. Then, by opening the economy to the rest of the world, the model not only shows which firms survive in the domestic market but also which ones export. Therefore, the most productive firms would not necessarily export, because export decision also depends on how effectively firms carry out a set of management practices to adapt their product to foreign demand. On the empirical side, productivity and management practices at firm level are measured by using several methods and specifications to identify their effect on exporter status, exploiting the waves of The World Bank Enterprise Surveys of 2006, 2010 and 2017 for Argentina. The main results indicate that both productivity and management practices positively affect the probability of being an exporter, and their effects are very similar in magnitude.